Integrated Analysis of Single-Cell and Bulk RNA-Sequencing Based on EcoTyper Machine Learning Framework Identifies Cell-State-Specific M2 Macrophage Markers Associated with Gastric Cancer Prognosis - Zhu AK; Li GY; Chen FC; Shan JQ; Shan YQ; Lv CX; Zhu ZQ; He YR; Zhai LL (ImmunoTargets and Therapy)
A-Kao Zhu,1,* Guang-Yao Li,2,* Fang-Ci Chen,3 Jia-Qi Shan,3 Yu-Qiang Shan,3,4 Chen-Xi Lv,3 Zhi-Qiang Zhu,5 Yi-Ren He,5 Lu-Lu Zhai5 1Department of Colorectal Surgery and Oncology, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310009, People’s Republic of China; 2Department of General Surgery, The Second People’s Hospital of Wuhu, Wuhu, 241000, People’s Republic of China; 3The Fourth School of Clinical Medicine, Zhejiang University of Traditional Chinese Medicine, Hangzhou, 310006, People’s Republic of China; 4Department of Gastrointestinal Surgery, Hangzhou First People’s Hospital Affiliated to Westlake University School of Medicine, Hangzhou, 310006, People’s Republic of China; 5Department of General Surgery, the First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lu-Lu Zhai; Yi-Ren He, Email jackyzhai123@163.com; heyiren2007@163.comBackground: Tumor is a complex and dynamic ecosystem formed by the interaction of numerous diverse cells types and the microenvironments they inhabit. Determining how cellular states change and develop distinct cellular communities in response to the tumor microenvironment is critical to understanding cancer progression. Tumour-associated macrophages (TAMs) are an important component of the tumour microenvironment and play a crucial role in cancer progression. This study was designed to identify cell-state-specific M2 macrophage markers associated with gastric cancer (GC) prognosis through integrative analysis of single-cell RNA sequencing (scRNA-seq) and bulk RNA-seq data using a machine learning framework named EcoTyper.Results: The results showed that TAMs were classified into M1 macrophages, M2 macrophages, monocytes, undefined macrophages and dendritic cells, with M2 macrophages predominating. EcoTyper assigned macrophages to different cell states and ecotypes. A total of 168 cell-state-specific M2 macrophage markers were obtained by integrative analysis of scRNA-seq and bulk RNA-seq data. These markers could categorize GC patients into two clusters (clusters A and B) with different survival and M2 macrophages infiltration abundance. Cell adhesion molecules, cytokine-cytokine receptor interaction, JAK/STAT pathway, MAPK pathway were significantly enriched in cluster A, which had worse survival and higher M2 macrophages infiltration.Conclusion: In conclusion, this study profiles a single-cell atlas of intratumor heterogeneity and defines the cell states and ecotypes of TAMs in GC. Furthermore, we have identified prognostically relevant cell-state-specific M2 macrophage markers. These findings provide novel insights into the tumor ecosystem and cancer progression.Keywords: Tumor-associated macrophages, Gastric cancer, Ecotype, Cell state, Prognosis